Problem Solving Process Based on the Newman Procedure in an Effort to Improve Students' Mathematical Reversible Thinking - Fatimah Sunusi (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2024)
Students' low Reversible Thinking and mathematical problem solving abilities, especially in working on mathematics problems in the form of stories. This research aims to determine and describe the increase in Reversible Thinking and problem solving abilities in mathematics problems in the form of stories after implementing the Newman Procedure in the learning and problem solving process. This type of research is the Kemmis and Taggart model of Class Action Research (PTK) which consists of 4 stages, namely planning, implementation, observation and reflection. This research was conducted in two cycles. Data collection techniques in this research are observation, tests, and documentation. The data analysis technique used is qualitative analysis to describe research results through observation and quantitative analysis techniques to analyze test assessment scores. The results of this research show an increase in students' reversible thinking abilities seen from changes in attitudes and behavior, seen from the ability to read questions quickly and clearly, able to understand the information contained in the reading, easy to transform information into mathematical language, confident to work on questions and able to take responsibility for the answers obtained.